Rancang Bangun Aplikasi Diagnosa Self Efficacy - Ningrum, Fitria Cahya; Soebagyo, Joko (International Journal of Progressive Mathematics Education, 2023)
Mathematical self-efficacy is a person's self-confidence in mathematics. The perceived ability of students towards mathematics lessons provides the right action in solving any math problems or real life in general. Diagnosing the level of self-efficacy can be done using the help of an application. Using a self-efficacy diagnostic application is the same as consulting an expert. The type of research conducted is Research and Development (R&D). The research method uses the ADDIE stages which include the analysis, design, development and implementation stages. The results of the study revealed that the media expert's average score was 4.05 (decent). Students' positive response to the self- efficacy diagnostic application developed was 3.5 or 85% which was classified as very good. So the self-efficacy diagnostic application can be used as an alternative to determine the level of students' self-efficacy towards mathematics